Visitando Clarice Lispector: alienação, identificação e repetição em “A hora da estrela” - Brito, Higor de Sousa (2023)
Literature as an artistic production has contributed and contributes greatly to humanity, being able to provoke in the reader a range of sensations. Psychoanalysis, in turn, in Freud and later with Lacan, intends to understand the human productions, its subjectivity, and how the unconscious makes itself present and goes through everything the subject produces, whether it is the symptom, the dream, the flawed act, its repetitions, etc. Hence, the present work explores, by means of an approximation between psychoanalysis and literature, the Lacanian concepts of alienation, repetition, and identification, being the latter also understood as a form of alienation. All these concepts are explored starting from a dialogue with literature, in particular, the work The Hour of the Star by Clarice Lispector. All these concepts are explored starting from a dialogue with literature, in particular, the work “The Hour of the Star” by Clarice Lispector. The present research is therefore established on a literature review, especially from a Lacanian point of view reading of Freud's work and commentators who contribute to the discussion of the studied themes. According to what we seek of showing, psychoanalysis and literature contribute mutually, in a degree of parity, not being subordinated to one another, and perhaps literature has much to teach us about the fields of possibility, particularly regarding interpretation. Furthermore, alienation through the Other appears to Lacan as a si ne qua non condition of subjectivity, and the complete separation being impossible. Lastly, we can conclude that both pairing psychoanalysis-literature and alienation-separation are themes of great complexity, on which we sought here to establish a starting point.